El Espíritu Santo en su índole trinitaria y esponsal según Guillermo de Saint Thierry - Reyes-Gacitúa, Eva (Verbum Vitae, 2020)
The theologian and mysticist William of St-Thierry elaborates a pneumatological thought centering around espousal dynamism. From this place, the author’s main formulations are reflected from Expositio super Cantica canticorum: First, placing love as a primacy of the Spirit on top of its understanding; second, from the progress of beauty to the source of every good, referring to lovers’ reciprocity and, finally, from the two to only one Spirit. From these axes, we intend to understand and analyze Unitas spiritus, as an economic event in the life of a believer, from whom our author articulates that the Holy Spirit makes possible the unity of Father God and Son, as well as that of God and mankind.